2011
DOI: 10.1016/j.ajpath.2011.03.034
|View full text |Cite|
|
Sign up to set email alerts
|

Abnormal Cell Properties and Down-Regulated FAK-Src Complex Signaling in B Lymphoblasts of Autistic Subjects

Abstract: Recent studies suggest that one of the major pathways to the pathogenesis of autism is reduced cell migration. Focal adhesion kinase (FAK) has an important role in neural migration, dendritic morphological characteristics, axonal branching, and synapse formation. The FAK-Src complex, activated by upstream reelin and integrin ␤1, can initiate a cascade of phosphorylation events to trigger multiple intracellular pathways, including mitogen-activated protein kinaseextracellular signal-regulated kinase and phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…These processes have been reported to be associated with ASD in the previous studies and our results were similar to these studies. For example, expression of FAK (focal adhesion kinase) was diminished in autistic lymphoblasts and overexpression of FAK in these cells restored the adhesion and migration defects . Besides ASDs, change in cytoskeleton proteins expression has been reported in other psychiatric disorders .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes have been reported to be associated with ASD in the previous studies and our results were similar to these studies. For example, expression of FAK (focal adhesion kinase) was diminished in autistic lymphoblasts and overexpression of FAK in these cells restored the adhesion and migration defects . Besides ASDs, change in cytoskeleton proteins expression has been reported in other psychiatric disorders .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent genetic studies demonstrate that alterations in synaptic genes including those encoding cell adhesion molecules and their interaction partners play important roles in the pathogenesis of ASD . Migration defects have also been proposed as one of the major pathways of autism …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sheikh et al (2010a,b) also found that the Bcl‐2 expression was significantly reduced in the frontal cerebral cortex and cerebellum of autistic subjects. Lymphoblast cell lines have been suggested to be a valuable tool for identifying genes associated with autism and provide an alternative approach for understanding the biology and genetics of autism (Baron et al, 2006; Wei et al, 2011). By examining Bcl‐2 protein expression in the lymphoblasts of autistic subjects and compare the results with age‐matched normal controls, Malik et al identified that Bcl‐2 protein expression is also significantly decreased in lymphoblasts of autistic subjects (Malik et al, 2011).…”
Section: Apoptosis‐related Proteins In Autismmentioning
confidence: 99%
“…Indeed, FAK expression is diminished in autistic lymphoblasts, and these cells show defects in migration, adhesion and proliferation (Wei et al ., ). Of note, overexpression of FAK in these cells restored the adhesion and migration defects (Wei et al ., ). Further studies link an influence of dysregulated FAK on the appearance of autism and schizophrenia.…”
Section: A Role For Fak In Neurological Diseasesmentioning
confidence: 97%
“…Migration defects have been proposed as one of the major pathways of autism. Indeed, FAK expression is diminished in autistic lymphoblasts, and these cells show defects in migration, adhesion and proliferation (Wei et al, 2011). Of note, overexpression of FAK in these cells restored the adhesion and migration defects (Wei et al, 2011).…”
Section: A Role For Fak In Neurological Diseasesmentioning
confidence: 99%